Partial ASN.1 - Choi, Sunwan
In many cases, the most time consuming part of the Open Systems Interconnection (OSI) protocol stack is the encoding and decoding of transfer syntax done in the presentation layer. The conventional ASN.1/BER decoding scheme runs on a whole Presentation Protocol Data Unit (PPDU). To overcome this problem, we present a new ASN.1/BER decoding scheme called Partial Decoding. The Partial Decoding scheme allows us to to start decoding partially on each segment of a PPDU before a whole PPDU has been received. The measures show that the new scheme has a performance improvement as high as 40% over the conventional decoding scheme at large message size. Parallel processing for the network layer through the presentation layer is also used for a high performance protocol implementation on the basis of the proposed scheme.
Keywords: ASN.1.; BER; OSI; Partial decoding scheme; Parallel implementation